The Relationship Between Knowledge and Personal Hygiene Genitalia During Menstruation In Adolescent Girls - Bahuwa, Septi Anggun Rukmana; Laleno, Nofita (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: During puberty, adolescent girls will experience menstruation, where they do not fully understand the importance of maintaining personal hygiene during menstruation. So health education is very important for adolescents. Health education can increase the knowledge of adolescent girls about maintaining personal hygiene during menstruation. Objective: This study is to determine the effect of knowledge on personal hygiene of genitalia during menstruation in adolescent girls. Methods: This study uses a type of literature review research, namely a study in the form of a literature review using the results of previous research and textbooks or research journals. To obtain data that is in accordance with the research topic, we conducted a search for national and international based journals in three data bases, namely Science Direct and GAoogle Scholar using. Results: the results of 5 journals found that there was an effect of knowledge on personal hygiene of genitalia during menstruation in adolescent girls. Conclusion: From the results of literature review searches from a total of 5 journals, it was found that there was an influence of knowledge on personal hygiene of genitalia during menstruation in adolescent girls. Keywords: knowledge, personal hygiene, hygiene, menstruation